2006
DOI: 10.1111/j.1469-7998.2006.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Niche overlap and resource partitioning between two sympatric fox species in southern Brazil

Abstract: Mechanisms that favour the co-occurrence of morphologically and ecologically similar species in South America are potentially relevant, because two or more species often occur in sympatry. In the present study, we investigated possible mechanisms of resource partitioning between two sympatric species of foxes, the crab-eating fox Cerdocyon thous and the pampas fox Pseudalopex gymnocercus, in the National Park of Aparados da Serra in southern Brazil (29110 0 S, 50105 0 W). We considered three main niche dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 33 publications
9
72
3
7
Order By: Relevance
“…Most of the carnivores we studied followed activity patterns previously known. The mostly nocturnal activity pattern has also been reported for crab-eating foxes in the Chaco-Chiquitano Transitional Forest of Bolivia (Maffei et al, 2002), in northeastern Argentina (Di Bitetti et al, 2009) and in southeastern Brazil (Vieira & Port, 2007). Ocelots were predominantly nocturnal in our study area, as also reported for the Bosque Chiquitano of Bolivia (Maffei et al, 2002), the Bolivian Amazon (Gómez et al, 2005), the Atlantic Forest of Argentina (Di Bitetti et al, 2006), and the Peruvian Amazon (Kolowski & Alonso, 2010).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Most of the carnivores we studied followed activity patterns previously known. The mostly nocturnal activity pattern has also been reported for crab-eating foxes in the Chaco-Chiquitano Transitional Forest of Bolivia (Maffei et al, 2002), in northeastern Argentina (Di Bitetti et al, 2009) and in southeastern Brazil (Vieira & Port, 2007). Ocelots were predominantly nocturnal in our study area, as also reported for the Bosque Chiquitano of Bolivia (Maffei et al, 2002), the Bolivian Amazon (Gómez et al, 2005), the Atlantic Forest of Argentina (Di Bitetti et al, 2006), and the Peruvian Amazon (Kolowski & Alonso, 2010).…”
Section: Resultssupporting
confidence: 68%
“…Data obtained from camera trapping can be used to study several topics of animal ecology such as inventories (Srbek-Araujo & Chiarello, 2005;Tobler et al, 2008), site occupancy (Mackenzie & Royle, 2005;O'Connell et al, 2006;Rich et al, 2013), patterns of spatial partitioning among species (Sarmento et al, 2011;Sollmann et al, 2012), temporal interactions between species as well as activity patterns (Foster et al, 2013;Frey et al, 2017). In the last two decades, several factors contributing to Neotropical carnivore coexistence have been studied using camera trapping (Vieira & Port, 2007;Di Bitetti et al, 2010;Bianchi et al, 2016). Additional applications of camera trapping include estimation of relative densities of elusive species Mackenzie et al, 2006), identification of critical habitats for threatened species and predicting their population trends (McCarthy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Isto se aplica a L. gymnocercus que tem o hábito de forragear solitariamente, ainda que ocupe uma área mé-dia de apenas 2,63km 2 (55-461 ha) (Lucherini & Luengos Vidal 2008), sem diferir entre machos e fêmeas (Luengos Vidal et al 2012). Ossos robustos seriam necessários para situações como manipular presas de maior porte ou para o nado (Martín-Serra et al 2014), o que não é o caso de L. gymnocercus cuja dietas baseia-se em roedores, coleópte-ros, pássaros, frutas e sementes e não têm hábitos semiaquáticos (Vieira & Port, 2007).…”
Section: Aspectos Funcionais E Evolutivosunclassified
“…Têm preferência por áreas abertas e planas com clima subúmido a seco (Lucherini & Luengos Vidal 2008). Digitígrados, nas áreas de sobreposição de dieta com Cerdocyon thous no Brasil, são os mais carnívoros (Vieira & Port 2007).…”
Section: Introductionunclassified
“…Quadros (2002) demonstrou a aplicação deste método na identificação de espécies de presas consumidas por predadores silvestres, analisando pelos encontrados em fezes. Vieira & Port (2007) e Abreu et al (2010) também se valeram deste método para determinar a espécie de predador através das amostras fecais dos mesmos e assim comparar a dieta de dois canídeos simpátricos no Rio Grande do Sul. Diversos autores já desenvolveram chaves de identificação de espécies baseadas exclusivamente em características tricológicas (Oli 1993, Perrin & Campbel 1979, Wallis 1993, Mathiak 1938, Ingberman & MonteiroFilho 2006.…”
Section: Introductionunclassified